The Vulnerable Dynamics of Discourse. (May 2021) - Giladi, Paul; Petherbridge, Danielle
Abstract: In this paper, we offer some compelling reasons to think that issues relating to vulnerability play a significant – albeit thus far underacknowledged – role in Jürgen Habermas's notions of communicative action and discourse. We shall argue that the basic notions of discourse and communicative action presuppose a robust conception of vulnerability and that recognising vulnerability is essential for (i) making sense of the social character of knowledge, on the epistemic side of things, and for (ii) making sense of the possibility of deliberative democracy, on the political side of things. Our paper is divided into four principal sections. In Section 1, we provide a basic outline of Habermas on communicative action and discourse. In Section 2, we develop an account of vulnerability and communication in the context of speaker/hearer relations. We specifically focus on distorted communication, vulnerability and speech. In Section 3, we focus on elaborating epistemic pathologies in the context of epistemic oppression and testimonial injustice. In Section 4, we focus on explaining how Habermasian resources contribute to vulnerability theory, and how introducing vulnerability theory to Habermas broadens or deepens his theory of communication action and his discourse ethics theory.